Validation of a 60K SNP chip for caribou (Rangifer tarandus) for use in wildlife forensics, conservation, and management - Trottier-Lavoie Mallorie; Prunier Julien; Poisson William; Carrier Alexandra; Gilbert Isabelle; Mastromonaco Gabriela; Albert Vicky; Cecilia Hernandez; Bourret Vincent; Taillon Joëlle; Droit Arnaud; Côté Steeve D.; et al. (Forensic Science International: Animals and Environments)
Large-scale genotyping platforms are currently being developed for several wild species. By querying thousands of polymorphic loci, genomics can be a useful ecological tool for describing and monitoring populations. Genomics is becoming increasingly useful as a forensic tool because of its ability to identify population of origin for purposes of enforcing anti-poaching laws. Our aim was to test the new SNP chip for caribou/reindeer (Rangifer tarandus) (Illumina iSelect caribou 60 K) under recommended and non-optimal sample conditions. Impact on signal detection (call rate) and error rate were assessed using reference samples. The SNP chip was shown to be robust, highly sensitive, reliable, and accurate at more than 10-fold below the recommended DNA input. Biological source of DNA had minor impact, even with fecal pellets given sufficient amount of host DNA. Hybridization of non-Rangifer samples as well as samples bearing DNA from two Rangifer samples both showed a drop in call rate and shifted levels of heterozygosity. Based on a population-targeted subset of SNPs included in the chip design, reassignment of 981 samples to a functional group (here to a caribou ecotype) was highly accurate (99.59 %) and the relative probability of reassignment error was estimated using the logarithm of odds score. Overall, the SNP chip is suitable for analysis of caribou/reindeer genomes even with suboptimal sampling and hence useful for population management and forensics.